2018
DOI: 10.5539/ies.v11n5p25
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Facilitating Knowledge Acquisition and Retention: An Inquiry into Magnetic Poles with Challenging Questions

Abstract: The current research is to give an example to the inquiry-based science teaching implementations for facilitating knowledge acquisition and retention in a short period of time. Thus, the aim of the research is to transfer of acquired knowledge into different situations using sequential inquiry activities, which have challenging questions for inquiry about what the magnetic pole is and how to discover it. The research was designed as a pre-experimental, one-group pre-test/post-test (N=65) with a retention-test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
(11 reference statements)
3
6
0
Order By: Relevance
“…When the responses of the students were examined, it was seen that students' agreements on non-scientific ideas took their least value in the university level. This finding showed parallelism with the research which reported more correct responses from teacher candidates as a result of the given instruction (Ince & Yilmaz, 2012;Okulu & Oğuz Ünver, 2018). Teacher candidates become experts in their field with the help of the university education.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…When the responses of the students were examined, it was seen that students' agreements on non-scientific ideas took their least value in the university level. This finding showed parallelism with the research which reported more correct responses from teacher candidates as a result of the given instruction (Ince & Yilmaz, 2012;Okulu & Oğuz Ünver, 2018). Teacher candidates become experts in their field with the help of the university education.…”
Section: Discussionsupporting
confidence: 84%
“…When the results obtained from item 4 were considered, it was realized that a relatively high percentage of agreements were obtained from university students (19.4%). This is also in line with the literature (Okulu & Oğuz Ünver, 2018). The researchers underlined the conduction of proper learning activities during courses and utilization of scientific inquiry for the elimination of those misconceptions.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations